Kontribusi Kunjungan Rumah terhadap Kesulitan Belajar Siswa - Solihatun Solihatun; Hayu Stevani; Sisca Folastri (ENLIGHTEN: Jurnal Bimbingan Konseling Islam, 2021)
Home visits are carried out to recognise family conditions related to problems faced by children, such as learning difficulties during the Covid-19 pandemic, students lack of concentration, do not understand the course material, and indifference in learning. The purpose of this study is to describe home visits, learning difficulties and to determine the contribution of home visits to students' learning difficulties. The research design in this study is quantitative with a simple regression analysis method. The population is 684 students using purposive sampling technique and recruiting as many as 65 students in class X. The instrument is the scale of home visits and learning difficulties. The results showed that home visits contributed to learning difficulties experienced by students by 12%. Based on the ANOVA test, it can be seen that the significance value of .005 which is smaller than .05. It can be concluded that home visits have a significant effect on student learning difficulties and the implications in guidance and counselling in the form of follow-up to guidance and counselling teachers in the implementation of group guidance services, content mastery and group counselling.